RESEARCH OF IT SERVICES MARKET OF UKRAINE - Shateev , O.V. (Global Prosperity, 2023)
The author conducted a study of the IT services market in Ukraine under modern conditions, covering several key aspects that reflect the dynamics of this sector’s development, its resilience to challenges, and its role in the country’s economy. The purpose of this article is to publish the results of the study of the IT services market in Ukraine. In writing the article, general and specialized scientific research methods were used. In particular, deductive and inductive methods were applied to analyze the IT market. An abstract-logical method was employed to summarize and substantiate the directions for the development of the IT market in Ukraine. Current conditions include both global technological trends and specific domestic challenges, such as war and economic instability, which have a significant impact on the IT market. It was established that the IT services market in Ukraine is considered one of the most important export sectors. According to data, Ukrainian IT companies provide a significant volume of services to foreign clients, especially in EU countries and the USA. This includes software outsourcing, IT consulting, mobile and web application development, as well as artificial intelligence and machine learning technologies. The demand for Ukrainian IT specialists remains high despite the military conflict, which confirms the stable level of IT services exports even during times of crisis. With the onset of a full-scale war in Ukraine, many companies were forced to adapt to new conditions, particularly through the relocation of their specialists to safer regions or abroad. Many companies were able to quickly implement hybrid or remote work models, which helped to maintain productivity. However, the war continues to impose limitations on operational activities, and therefore, the study examines new models of management and support for specialists during the crisis period. It is substantiated that one of the main aspects of IT market research in Ukraine is the analysis of the personnel situation. Ukraine has always been known for its large number of highly qualified IT specialists. However, the war has provoked a certain degree of migration of specialists abroad, creating a shortage in the local market. At the same time, some Ukrainian IT companies continue to hire employees remotely, partially compensating for the personnel shortage in Ukraine. The study also includes an analysis of opportunities for professional growth and development to ensure the competitiveness of Ukrainian specialists in the global market. It has been proven that the IT services market in Ukraine under modern conditions demonstrates stability, flexibility, and the ability to adapt to global and domestic challenges, continuing to play an important role in the country’s economy.